Induction and Recovery of the Viable but Nonculturable State of Hop-Resistance Lactobacillus brevis - Liu, Junyan; Deng, Yang; Soteyome, Thanapop; Li, Yanyan; Su, Jianyu; Li, Lin; Li, Bing; Shirtliff, Mark E.; Xu, Zhenbo; Peters, Brian M. (Frontiers in Microbiology, 2018)
Lactobacillus brevis is a major hop-resistance bacterium capable of entering into the viable but nonculturable (VBNC) state. Due to difficulty or incapability in detection by routine culturing methodology and its beer spoilage ability, L. brevis poses significant challenge for the brewing industry. This study aimed at investigating the VBNC state of a hop-resistance strain, L. brevis BM-LB13908. The culturable, total and viable numbers of L. brevis cells were calculated by MRS agar plate counting, acridine orange direct count (AODC) method and Live/Dead BacLight bacterial viability kit with fluorescence microscope. VBNC formation was induced by 189 ± 5.7 days under low-temperature storage or 27 ± 1.2 subcultures by continuous passage in beer, and VBNC cells induced by both strategies were recovered by addition of catalase. In addition, insignificant difference in beer-spoilage ability was found in 3 states of L. brevis, including logarithmic growing, VBNC and recovered cells. This is the first study on the formation of VBNC state for L. brevis and beer-spoilage ability of both VBNC and recovered cells, which indicate L. brevis strain could cause beer spoilage without being detected by routine methodologies. The results derived from this study may aid in further study on L. brevis and other hop-resistance bacteria, and guidance on the prevention and control of beer spoilage, such as improvement for brewers on the microbiological quality control by using the improved culture method with catalase supplementation.